2020
DOI: 10.1186/s13012-020-01018-7
|View full text |Cite
|
Sign up to set email alerts
|

Public target interventions to reduce the inappropriate use of medicines or medical procedures: a systematic review

Abstract: Background An epidemic of health disorders can be triggered by a collective manifestation of inappropriate behaviors, usually systematically fueled by non-medical factors at the individual and/or societal levels. This study aimed to (1) landscape and assess the evidence on interventions that reduce inappropriate demand of medical resources (medicines or procedures) by triggering behavioral change among healthcare consumers, (2) map out intervention components that have been tried and tested, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 106 publications
(154 reference statements)
0
4
0
Order By: Relevance
“…A recent systematic review focused on non-clinical programs to reduce the inappropriate or unnecessary use of medicines observed that interventions consisting of education messages and recommended behavior alternatives were more likely to be successful in reducing the inappropriate use of medicines or medical procedures ( Lin et al, 2020 ). Educational strategies are essential to improve prescription, as observed by Amorim et al (2021) since physician-related characteristics can influence the number of PIM prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review focused on non-clinical programs to reduce the inappropriate or unnecessary use of medicines observed that interventions consisting of education messages and recommended behavior alternatives were more likely to be successful in reducing the inappropriate use of medicines or medical procedures ( Lin et al, 2020 ). Educational strategies are essential to improve prescription, as observed by Amorim et al (2021) since physician-related characteristics can influence the number of PIM prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Often AMS has failed to make a convincing case for itself and justify the resources it deserves from the management without which it cannot function (5,8). Behavioural change has been demonstrated to be one of the most difficult things to achieve but persistent reinforcement of the message increases the chances for success (11,18). This applies when trying to persuade managers and prescribers in healthcare providing institutions of the need to formally incorporate it into their healthcare policy and adopt new prescribing behaviours respectively (9).…”
Section: Discussionmentioning
confidence: 99%
“…[9] Dr. Lin also identified the research gap that public target interventions were absent in low-to-middle-income settings. [8] According to our data (unpublished), most of the interventions aiming to reducing inappropriate antibiotic use in China were implemented in primary care settings to reduce inappropriate antibiotic prescribing, largely ignoring demand-side factors, and sociocultural determinants were scarcely embedded in the intervention designs. Therefore, we very much agree with the correspondents that few interventions J o u r n a l P r e -p r o o f tailored the interventions to specific settings and individuals; campaign should convey information targeting on multiple components, such as incorporating theory-grounded framework in our recent publication (the Health Belief Model and Socio-ecological Model).…”
mentioning
confidence: 99%
“…[7] To address the gap, Dr. Lin led an Implementation Science systematic review in 2020 identifying 25 public target intervention studies with behavioural change techniques aiming to reducing unnecessary antibiotic use. [8] Most of them conducted campaigns for public education and were in high-income settings. However, intervention assessments revealed that conveying knowledge to the public did not change people's attitudes and behaviours.…”
mentioning
confidence: 99%